Needs for sexual and reproductive health education for students with hearing impairment in Buleleng District, Bali Province - Nyoman Sri Ariantini; Desak Putu Yuli Kurniati; Dyah Pradnyaparamita Duarsa (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: Adolescents with hearing impairment face a number of exclusion due to their limitation, including lack of access to information on reproductive health. This study aims to explore needs for sexual and reproductive health education for students with hearing impairment at Singaraja. Methods: A qualitative study was conducted at Buleleng District. Data were collected through in-depth interviews to 19 informants. Informants were purposively selected based on their specific roles. Our informants included students with hearing impairment, head of school, teachers and parents or carers. Data were analysed using a thematic approach. Results: The majority of students with hearing impairment had low level of knowledge associated to sexual and reproductive health. However, sexual and reproductive health practices between adolescents with and without hearing impairment were generally comparable. Needs for sexual and reproductive health education must cover several elements: (1) education material must be tailored based on age, (2) learning methods should be tailored based on their intellectual ability, and (3) learning methods must use contextual and real model approach to allow better transfer of information. Teachers faced difficulty to provide sexual and reproductive health education for students with hearing impairment even though some modules are already available. Conclusions: The provision of sexual and reproductive health education for students with hearing impairment requires tailored material, simple and attractive learning methods, and visual media. Further analysis of the existing reproductive health education curricula for students with hearing impairment is required in order to ensure fulfilment of reproductive rights of adolescent with special needs.